“SEMAMPAI” SEHAT, MANAJERIAL, MANDIRI, DAN PANDAI: KKN-PPM, MUARA ANCALONG, KUTAI TIMUR - Rudy Agung Nugroho; Ari Susandy Sanjaya; Iwan Muhammad Ramdan; Rudianto Rudianto; Widha Prahastika (Universitas Muhammadiyah Tapanuli Selatan, 2021)
Community Development Program-learning and community service program or Kuliah kerja nyata-pembelajaran dan pengabdian kepada masyarakat (KKN-PPM) which is a form of community service has been done from July-August 2019 in the Kelinjau Ulu and Kelinjau Ilir village, Muara Ancalong, East Kutai, East Kalimantan. The purpose of the KKN-PPM was to empower the community to be more productive. The theme of the KKN-PPM program was